Publication Reviews. Issue 1 (1st March 2016) - Briggs-Goode, Amanda; Olding, Simon; Clarkson, Dr Verity
BE.HIVE UK Pavilion, Wolfgang Buttress (2015) Nottingham, UK: Wolfgang Buttress Studio, 128 pp., ISBN: 9780993285509, s/bk, £32.00The Walter C. Koerner Collection of European Ceramics: A Discerning Eye, Carol E. Mayer (2014) Vancouver: Museum of Anthropology, the University of British Columbia, 172 pp., ISBN: 9781927958186, h/bk, 45.00Crafting Design in Italy: From Post-War to Postmodernism, Catharine Rossi (2015) Manchester: Manchester University Press, 219 pp., ISBN: 9780719089404, h/bk, £70.00